Pedagogical practices and methodologies of teachers are fundamental in the literacy process (Research, Society and Development, 2018)
From a bibliographical point of view, this article aims to reflect on the inclusion and appreciation of pedagogical practices and methodologies used in school spaces by teachers, through methods for literacy in the first years of elementary school, since traditional approaches to the sociolinguistic approach, has as main objective to literacy and literacy, and to point to reading as a fundamental practice because through reading and writing skills, the child inserts himself into "social practices", understanding the world around him, that can bring more charm to the child while learning, thus avoiding that it presents difficulties in its action when learning.